Diversity and functions of fungal VOCs with special reference to the multiple bioactivities of the mushroom alcohol - Guohua Yin; Geromy G. Moore; Joan Wennstrom Bennett (Mycology)
Different species of fungi usually share many common pathways but they also have some unique metabolic pathways (e.g. those for specialised metabolites). It is not clear how gene expression patterns significantly contribute to the creation of diverse volatile compounds. Based on the research of most VOCs, the functions of different fungal volatile compounds are mainly as follows: inhibitory or synergistic effects on other microorganisms, promoting growth in plants or inducing a defensive response in crops, and participating in the material cycle or affecting the interactions between organisms in the ecosystem. Approximately three hundred VOCs have been identified from fungi. According to their chemical properties, the major categories of fungal VOCs are terpenoids, aromatic compounds, alcohols, alkanes, esters, aldehydes, ketones, and heterocyclic compounds. The eight-carbon alcohol (1-octen-3-ol) is one of the most characteristic fungal VOC. This abundantly produced VOC results from the breakdown of linoleic acid and causes a distinctive mushroom-like odour. Consequently, its presence has been utilised as a signal of fungal growth. It is also produced by certain plants and functions as a semiochemical for numerous arthropods. The use of Drosophila melanogaster (fruit flies) as a model for testing the toxicity of fungal VOCs showed that some VOCs delayed metamorphosis and/or caused fly death at certain concentrations. When Drosophila was cultivated in an atmosphere shared with VOC mixtures released from growing cultures of several medically important fungi, including Aspergillus fumigatus, toxicity was observed. Additionally, we propose that components of the genetic immune system of D. melanogaster are engaged in the toxicity of fungal VOCs mainly via the elicitation of the Toll pathway. The presence of 1-octen-3-ol, for example, was associated with higher levels of toxicity in the fruit fly bioassay. In this review, we summarise (1) the diversity and functions of different fungal VOCs, (2) the biosynthesis and bioactive characteristics of 1-octen-3-ol, and (3) the use of D. melanogaster as a genetic model to assess the health impacts of fungal VOCs.